Roof cooling techniques : a design handbook - Yannas, Simos; Erell, Evyatar; Molina, Jose Luis (London : Earthscan, 2006)
Accompanying CD-ROM contains ...'software that enables readers to evaluate their own designs.'--P. [4] of cover
Book is accompanied by 1 computer laser optical disc, entited'Roof cooling techniques : a design handbook : performance of radiative and evaporative cooling techniques of roofs' bearing the same call number and available at Bahagian Koleksi Media
Includes bibliographical references and index
Keywords: Roofs -- Cooling; Roofs -- Design and construction; Roofs -- Thermal properties; Buildings -- Environmental engineering